PENGARUH LINGKUNGAN KELUARGA, KEDISIPLINAN SISWA, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA DI SMA NEGERI 7 SURABAYA - Chulsum, Umi (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aims to: analyze the influence of family environment on learning outcomes at economics lesson of students in high school economics Negeri 7 Surabaya, analyze the influence of students dicipline on learning outcomes in economics lesson of student at SMAN 7 Surabaya, analyze the influence of learning motivation on learning outcomes in economics lesson of student at SMAN 7 Surabaya, and also the impact of family environment, students dicipline and learning motivation at the same time on the learning outcomes on economics lesson of student at SMAN 7 Surabaya. This research is quantitative. The population in this research were students of class X and class XI IPS at SMA Negeri 7 Surabaya year 2014-2015 as many as 228 students, while the number of samples used as much as 145 students. The data collection techniques that used are questionnaires, interviews, and documentation. Methods of analysis using multiple linear regression techniques. The results showed that : there is a significant and positive effect between family environment on learning outcomes in economics lesson of student at SMAN 7 Surabaya, a significant and positive effect between students dicipline on learning outcomes in economics lesson of student at SMAN 7 Surabaya, a significant and positive effect between learning motivation on learning outcomes in economics lesson of student at SMAN 7 Surabaya, and a significant and positive relations between family environment, student discipline and learning motivation jointly toward learning outcomes on economics lesson of students at SMAN 7 Surabaya